Granulocyte colony-stimulating factor and drugs elevating extracellular adenosine synergize to enhance haematopoietic reconstitution in irradiated mice - Pospísil, M; Hofer, M; Znojil, V; Netíková, J; Vácha, J; Holá, J; Vacek, A (European journal of haematology, 1998)
The activation of adenosine receptors has recently been demonstrated to stimulate haematopoiesis. In the present study, we investigated the ability of drugs elevating extracellular adenosine to influence curative effects of granulocyte colony-stimulating factor (G-CSF) in mice exposed to a sublethal dose of 4 Gy of 60Co radiation. Elevation of extracellular adenosine in mice was induced by the combined administration of dipyridamole, a drug inhibiting the cellular uptake of adenosine, and adenosine monophosphate (AMP), an adenosine prodrug. The effects of dipyridamole plus AMP, and G-CSF, administered either alone or in combination, were evaluated. The drugs were injected to mice in a 4-d treatment regimen starting on d 3 after irradiation and the haematopoietic response was evaluated on d 7, 10, 14, 18 and 24 after irradiation. While the effects of G-CSF on the late maturation stages of blood cells, appearing shortly after the completion of the treatment, were not influenced by dipyridamole plus AMP, positive effects of the combination therapy occurred in the post-irradiation recovery phase which is dependent on the repopulation of haematopoietic stem cells. This was indicated by the significant elevation of counts of granulocyte-macrophage progenitor cells (GM-CFC) and granulocytic cells in the bone marrow (d 14), of GM-CFC (d 14), granulocytic and erythroid cells (d 14 and 18) in the spleen, and of neutrophils (d 18), monocytes (d 14 and 18) and platelets (d 18) in the peripheral blood. These effects suggest that the repopulation potential of the combination therapy lies in a common multilineage cell population. The results of this study implicate the promising possibility to enhance the curative effects of G-CSF under conditions of myelosuppressive states induced by radiation exposure.
Keywords: Animals; Dipyridamole; Adenosine; Female; lymfocyty; dipyridamol; ženské pohlaví; Hematopoietic Stem Cells; Receptors, Purinergic P1; trombocyty; erytrocyty; adenosin; Mice; adenosinmonofosfát; monocyty; purinergní receptory P1; Platelet Aggregation Inhibitors; Mice, Inbred BALB C; myši; Blood Platelets; faktor stimulující kolonie granulocytů; Granulocyte Colony-Stimulating Factor; Monocytes; Granulocyte-Macrophage Colony-Stimulating Factor; Erythrocytes; granulocyty; Male; Mice, Inbred CBA; myši inbrední BALB C; Drug Synergism; hematopoetické kmenové buňky; synergismus léků; Lymphocytes; inhibitory agregace trombocytů; Granulocytes; zvířata; mužské pohlaví; myši inbrední CBA; faktor stimulující granulocyto-makrofágové kolonie; Adenosine Monophosphate